BUSINESS DEVELOPMENT STRATEGY OF SMALL AND MEDIUM ENTERPRISES DURING COVID-19 CONDITION IN THE COFFEE SHOP CULINARY INDUSTRY SECTOR IN BOGOR CITY - Cindi Dyah Widawati; Karuniana Dianta Arfiando Sebayang; Saparuddin M (Transpublika Publisher, 2022)
The research aims to determine: (1) the coffee shop profile of Halaman Belakang and Sisi Kiri, Bogor; (2) the development strategy implemented by the coffee shop in maintaining their business amidst the covid-19 pandemic; (3) The role of the coffee shop culinary industry in local economic growth, especially in the city of Bogor. This research is a qualitative descriptive study. This research was conducted in Bogor City in May – June 2022. The subjects of this research are coffee shop owners who have established their outlets since before the COVID-19 pandemic there are Halaman Belakang and Sisi Kiri. The results obtained from this study are that there are several strategies used by Halaman Belakang and Sisi Kiri in maintaining their business in the midst of a pandemic and still surviving until after the pandemic. One of them is the strategy of expanding marketing with promotions through events that have a very positive impact on the progress of the business run by Halaman Belakang and Sisi Kiri. The increasing number of coffee shops at this time has a positive effect on the development of the local economy at Bogor City, at this time coffee shops are one of the SMEs that are currently hype and absorb a lot of the workforce in the Bogor City. We hope this strategy can be implemented and become a consideration for other business owners in dealing with economic problems in Indonesia, especially to maintain their businesses.